Systems Theory and Management - Johnson, Richard A.; Kast, Fremont E.; Rosenzweig, James E. (Management Science, 1964)
Ludwig von Bertalanffy, in 1951, and Kenneth Boulding, in 1956, wrote articles which have provided a modern foundation for general systems theory [Bertalanffy, L. von. 1951. General system theory: A new approach to unity of science. Human Biol. (December) 303–361; Boulding, K. 1956. General systems theory: The skeleton of science. Management Sci. (April) 197–208.]. We build on that foundation in applying general systems theory to management. The general theory is reviewed for the reader. Next, it is applied as a theory for business, and an illustrative model of the systems concept is developed to show the business application. Finally, the systems concept is related to the traditional functions of a business, i.e., planning, organizing, control, and communications.